The Effectiveness Of The Responsibility Of The Ministry Of Republic Of Indonesia Atr / Bpn On The Implementation Of Online Locket Services In The Kendal District Land Office - Farahdiba Fitriani Bachtiar (Sultan Agung Notary Law Review, 2020)
The State of Indonesia is known for its abundant natural wealth, land is one of the natural resources and also the main capital owned by Indonesia to support this natural wealth. Land administration in Indonesia is carried out by the National Land Agency. The objectives of this study are to: (1) analyze and also explain that the National Land Agency changes non-online services to online services into online services, (2) Analyzes and also explores how the effectiveness of the Land Deed Making Officials' responsibilities in implementing online counter services made by ATR / BPN, (3) Analyze and also provide solutions related to problems that occur at the National Land Office. The approach method in this research is juridical empirical. The research specification used is descriptive. Sources of data used in this study consist of primary legal data, secondary legal data. Methods of data collection using literature studies and interviews, research locations in Kendal district, data analysis methods using deductive logic, followed by identifying legal discussions, the last step is to interpret and also construct legal materials. The research problems were analyzed by using the theory of benefit and also the theory of legal certainty. Based on this research, it can be concluded that: (1) Long queues and also difficult to control make the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency create computer-based services that aim to carry out Land Management. (2) The PERMATA Online Counter service made by the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency of Kendal Regency is arguably not effective enough because the server's limited menu is not completely perfect. (3) the obstacles that have been faced by the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency related to effectiveness related to the Online Counter Service system of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency in Kendal Regency, one of the obstacles is the lack of human resources.